Massive release of the histamine‐degrading enzyme diamine oxidase during severe anaphylaxis in mastocytosis patients. Issue 3 (1st January 2019) - Boehm, Thomas; Reiter, Birgit; Ristl, Robin; Petroczi, Karin; Sperr, Wolfgang; Stimpfl, Thomas; Valent, Peter; Jilma, Bernd
Abstract: Background: Histaminolytic activity mediated by diamine oxidase (DAO) is present in plasma after induction of severe anaphylaxis in rats, guinea pigs, and rabbits. Heparin released during mast cell degranulation in the gastrointestinal tract might liberate DAO from heparin‐sensitive storage sites. DAO release during anaphylaxis has not been demonstrated in humans. Methods: Plasma DAO, tryptase, and histamine concentrations of four severe anaphylaxis events were determined at multiple serial time points in two patients with systemic mastocytosis. The histamine degradation rates were measured in anaphylaxis samples and in pregnancy sera and plasma with comparable DAO concentrations. Results: Mean DAO (132 ng/mL) and tryptase (304 ng/mL) concentrations increased 187‐ and 4.0‐fold, respectively, over baseline values (DAO 0.7 ng/mL, tryptase 76 ng/mL) during severe anaphylaxis. Under non‐anaphylaxis conditions, DAO concentrations were not elevated in 29 mastocytosis patients compared to healthy volunteers and there was no correlation between DAO and tryptase levels in mastocytosis patients. The histamine degradation rate of DAO in plasma from mastocytosis patients during anaphylaxis is severely compromised compared to DAO from pregnancy samples. Conclusion: During severe anaphylaxis in mastocytosis patients, DAO is likely released from heparin‐sensitive gastrointestinal storage sites. The measured concentrations can degrade histamine, but DAO activity is compromised compared to pregnancy samples. For accurate histamine measurements during anaphylaxis, DAO inhibition is essential to inhibit further histamine degradation after blood withdrawal. Determination of DAO antigen levels might be of clinical value to improve the diagnosis of mast cell activation. Abstract : Diamine oxidase (DAO) antigen increases more than 100‐fold in plasma during severe anaphylaxis and degrades histamine (HIS) in vivo and in vitro but its activity is reduced compared to DAO in pregnancy plasma. Only immediate DAO inhibition after blood withdrawal allows accurate histamine measurements in plasma. Determination of DAO antigen levels might help to diagnose mast cell (MC) activation.